Canine Distemper Virus Selectively Inhibits Apoptosis Progression in Infected Immune Cells - Pillet, Stéphane (American Society for Microbiology (ASM), 2009)
Morbillivirus infections are characterized by severe leukopenia and immune suppression that develop even before the onset of clinical signs. To characterize in more detail the fate of the immune cells during the critical first week, we evaluated the overall viability, level of apoptosis, cell cycle status, and extent of infection in different immune tissues of ferrets inoculated with a lethal canine distemper virus (CDV) strain. Initial experiments with MDCK cells, a canine epithelial cell line, revealed that CDV infection resulted in only a marginal increase in apoptosis at high infection levels and that infected cells were more resistant to chemically induced apoptosis. In ferrets, levels of viability and early and late apoptosis remained stable in thymus and lymph node, where more than 80% of cells were infected, whereas a gradual albeit small increase in apoptosis was observed in peripheral blood mononuclear cells and spleen. Furthermore, the progression of spontaneous apoptosis in infected cells was inhibited, while the proportion of apoptotic noninfected “bystander” cells increased. The distribution of cells in the different stages of the cell cycle in the bone marrow was not affected, but dividing cells in the thymus decreased by 50%, and a 10-fold increase in cell division was noted in the spleen. It is unlikely that the extent of infection-induced cell death and cell cycle alterations alone can account for the dramatic leukopenia observed in this model. The investigation of additional mechanisms is therefore warranted.